2011
DOI: 10.1007/s00256-011-1288-y
|View full text |Cite
|
Sign up to set email alerts
|

CT-guided cervical nerve root injections: comparing the immediate post-injection anesthetic-related effects of the transforaminal injection with a new indirect technique

Abstract: The indirect cervical nerve root injection procedure is a potentially safer alternative to direct cervical transforaminal nerve root injections. The short-term pain reduction is similar using the two injection methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(41 citation statements)
references
References 25 publications
4
36
0
1
Order By: Relevance
“…With our study we present the first long term outcomes of indirect cervical nerve root blocks. We confirm the good short term outcomes similar to the study by Sutter et al [18] and can even show further improvement of pain relief and 'patients global impression of change' with the long term results particularly in patients who did not require surgery. Although most MRI abnormalities were not associated with 'improvement' at the various post-injection time points, the specific finding of disc extrusion was predictive for the likelihood of surgical treatment.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…With our study we present the first long term outcomes of indirect cervical nerve root blocks. We confirm the good short term outcomes similar to the study by Sutter et al [18] and can even show further improvement of pain relief and 'patients global impression of change' with the long term results particularly in patients who did not require surgery. Although most MRI abnormalities were not associated with 'improvement' at the various post-injection time points, the specific finding of disc extrusion was predictive for the likelihood of surgical treatment.…”
Section: Discussionsupporting
confidence: 90%
“…This is due to the larger distance to the vessels including the vertebral artery with less potential for complications such as arterial dissection or injection of drugs in brain-supplying arteries. Reported complications from the traditionally used direct cervical nerve root blocks include spinal cord and brain infarction which occur by penetrating the vertebral artery, the nerve root artery [5,[8][9][10][11][12][13][14][15][16][17][18] and small arteries in the intervertebral foramen [7]. Hodler et al reported two detrimental complications after technically correct direct cervical nerve root with cervical myelopathy and complete tetraplegia as well as persisting severe deficiencies after rehabilitation [5].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When MR images are unavailable for procedural planning, reschedule the injection or (117). After reports of catastrophic neurologic injuries from cervical NRBs, some investigators recommended protocol modifications (55,75,92,(118)(119)(120). Potentially safer techniques include extraforaminal needle placement, a lateral or posterior approach, digital At S1, the needle (N4) crosses the posterior S1 foramen and enters the epidural space inferior to the S1 pedicle.…”
Section: How I Do It: Spinal Injections For Pain Management Palmermentioning
confidence: 99%
“…In more than 8000 cervical, thoracic, and lumbar interventions performed by me or under my supervision, none have been complicated by hemorrhage, infection, or neurologic damage. Radiologists should recognize and tomography (CT) to guide needle placement (74)(75)(76)(77)(78)(79)(80). This preference reflects training experience, resource availability, and institutional policy.…”
Section: Risk and Risk Mitigationmentioning
confidence: 99%